Correspondence and Writing Materials of the Uzbek Khanates - Dilafruz Akhmedova Khusan kizi (Zien Journals, 2024)
This article examines the rules of documentation and letter writing, as well as the materials used for this purpose, in the Bukhara, Khiva, and Kokand Khanates from the mid-18th to the late 19th century. The information presented is based on letters found in the I-125 fund, 2nd inventory list of the National Archives of Uzbekistan.
Keywords: Uzbekistan; documentation; National